مفهوم العلمانية وموقف الإسلام منها (دراسة نقدية) - Amir Sahidin (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2022)
Secularism is a thought born from Western perspectives and experiences in particular, trying to separate religion from politics and public life. This thought is certainly very contrary to the teachings of Islam. However, secularism has had a wide impact, both in the West itself and in the Islamic world. Therefore, this article will examine secularism and Islamic attitudes related to it. Through literature review or library research with a critical analysis approach, it can be concluded that, first: secularism which in Arabic is called 'ilmaniyah, is not related at all to the word science or 'ilm in Arabic. Second; secularism exists because of the Western experience which is certainly different from Islamic society, such as the tyranny of the adherents of the Church Religion (Christian); and the conflict between science and the Church. Third: the attitude of Islam in this regard is that Islam strongly rejects the idea of ​​secularism, both in the form of separating religion from politics and from social life. Because both are very far from the call of Islam which is monotheistic, and the state (politics) is an important matter for upholding the Shari'a and the religion of Islam itself.